Macroeconomic Fluctuations and Equilibrium Discount Factors - Kramer, Charles (Washington, D.C. : International Monetary Fund, 1996)
The estimation of discount factors is a central issue in empirical finance, particularly in the literature on excess volatility. In particular, it is difficult to find empirical discount factors that are volatile enough to account for fluctuations in asset prices. This paper constructs discount factors from some macroeconomic time series commonly used in empirical models of asset prices. Data for the U.S. stock market imply some evidence that discount factors relate to macroeconomic conditions, but comparison of the estimated discount factors to Hansen-Jagannathan (1991) bounds shows that the candidate discount factors cannot account for the volatility in asset returns.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet